El presupuesto público y su relación con el cumplimiento de metas en la Municipalidad Distrital de Belén 2024 - Ramirez Isuiza, Diego Dino Augusto (2025)
The purpose of this study was to determine the relationship between the public budget and the achievement of goals by the District Municipality of Belén during the year 2024. The research was conducted using a quantitative, applied approach, with a non-experimental methodological design and a descriptive level. The sample consisted of 60 employees from the entity, who participated by answering questionnaires validated through content analysis. The reliability of the instruments was determined using Cronbach's alpha coefficient, obtaining a value of 0.857 for the public budget variable and 0.697 for the goal achievement variable. The results showed a significant positive correlation between both variables, with a Spearman coefficient of 0.728 and a significance level of p < 0.01, indicating a strong and statistically significant positive relationship.